Enhancing catalytic pyrolysis of polypropylene using mesopore-modified HZSM-5 catalysts: insights and strategies for improved performance - He, Qing; Akin, Oguzhan; Ureel, Yannick; Yazdani, Parviz; Li, Lingfeng; Varghese, Robin John; Van Geem, Kevin M. (Frontiers in Chemical Engineering, 2024)
Designing an active, selective, and stable catalyst for catalytic polyolefin pyrolysis is crucial for enhancing energy efficiency and economic viability in chemical processes. In this study, two synthesis methods—NaOH and NaOH/CTAB treatments—were employed to modify the physicochemical properties of CBV23, CBV55, and CBV80 zeolites. The catalytic performance of both parent and modified zeolites was evaluated for polypropylene pyrolysis using a two-stage micro-pyrolyzer coupled with two-dimensional GC-FID/MS. The NaOH/CTAB treatment preserved and enhanced strong acid sites while promoting a more uniform mesopore distribution. Among the catalysts tested, the hierarchical CBV80-ZM exhibited the best performance, achieving a propylene yield of 41 wt% and total light olefin and MA yields of 92 wt%. The improved catalytic performance was attributed to optimized acidity and larger pore size, which reduced the number of weak acid sites. These findings offer valuable insights for designing tailored zeolites based on specific target products for catalytic pyrolysis of plastic waste, particularly in the production of propylene and other high-value chemicals.